Alkaline Liquid Ventilation of the Membrane Lung for Extracorporeal Carbon Dioxide Removal (ECCO2R): In Vitro Study - Luigi Vivona; Michele Battistin; Eleonora Carlesso; Thomas Langer; Carlo Valsecchi; Sebastiano Maria Colombo; Serena Todaro; Stefano Gatti; Gaetano Florio; Antonio Pesenti; Giacomo Grasselli; Alberto Zanella (Membranes, 2021)
Extracorporeal carbon dioxide removal (ECCO2R) is a promising strategy to manage acute respiratory failure. We hypothesized that ECCO2R could be enhanced by ventilating the membrane lung with a sodium hydroxide (NaOH) solution with high CO2 absorbing capacity. A computed mathematical model was implemented to assess NaOH–CO2 interactions. Subsequently, we compared NaOH infusion, named “alkaline liquid ventilation”, to conventional oxygen sweeping flows. We built an extracorporeal circuit with two polypropylene membrane lungs, one to remove CO2 and the other to maintain a constant PCO2 (60 ± 2 mmHg). The circuit was primed with swine blood. Blood flow was 500 mL × min−1. After testing the safety and feasibility of increasing concentrations of aqueous NaOH (up to 100 mmol × L−1), the CO2 removal capacity of sweeping oxygen was compared to that of 100 mmol × L−1 NaOH. We performed six experiments to randomly test four sweep flows (100, 250, 500, 1000 mL × min−1) for each fluid plus 10 L × min−1 oxygen. Alkaline liquid ventilation proved to be feasible and safe. No damages or hemolysis were detected. NaOH showed higher CO2 removal capacity compared to oxygen for flows up to 1 L × min−1. However, the highest CO2 extraction power exerted by NaOH was comparable to that of 10 L × min−1 oxygen. Further studies with dedicated devices are required to exploit potential clinical applications of alkaline liquid ventilation.